Development of a building-specific life cycle sustainability assessment model - Liu, Siyu (2019)
The construction industry is of high economic signiﬁcance and has strong environmental and social impacts, and thus sustainable construction has attracted wide attention in the industry. In order to aid in the shift towards sustainable construction, there is a need to develop a reliable model for building sustainability assessment that encompasses three dimensions of sustainability and long-term impacts and is able to facilitate sustainability-oriented decision-making. Having recognized such research need, this study developed a building-specific life cycle sustainability assessment (LCSA) model, which integrated three life-cycle based methods, namely environmental life cycle assessment (E-LCA) for environmental impact evaluation, life-cycle cost analysis (LCCA) for economic analysis and social life cycle assessment (S-LCA) for social acceptability evaluation. Firstly, a conceptual framework for LCSA model was established through extracting impact categories from three life-cycle-based methods. Economic aspect was evaluated using life-cycle costs. Environmental impact categories were extracted from a selected environmental life cycle impact assessment method, which is ReCiPe endpoint approach in this study. As for social impact assessment, impact categories were selected using stakeholder-based approach. Four groups of stakeholders were identified, including worker, occupant, local community and society. This was followed by the identification of impact subcategories through content analysis. Secondly, a building-specific social life cycle impact assessment (S-LCIA) method was proposed. Indicators were selected for each subcategory based on the assessment objective and data availability. They were categorized into three groups, including quantitative indicators in generic analysis, as well as quantitative and semi-quantitative indicators in site-specific analysis; corresponding scoring methods were also provided. Weights among impact subcategories were generated through questionnaire survey based on consistent fuzzy preference relation (CFPR) based analytic hierarchy process (AHP) method, and weights among life-cycle phases were determined considering the possibility to impose measures to control as well as level of concern of construction practitioners. Thirdly, to address the issue of uncertainty of E-LCA studies, and more specifically the uncertainty induced by input parameters, a comparative assessment on global sensitivity analysis (GSA) methods was conducted. Focusing on sampling-based GSA methods, the assessment started by comparing three sampling methods regarding convergence rate and computation effort. This was followed by the comparison of four GSA methods, whereby each method was evaluated on its capability in explaining total output variance as well as the ranking of variance contribution of individual input parameters. Accordingly, suggestions were given on characterizing uncertainties through GSA. Finally, an integrated LCSA model was established based on fuzzy ELECTRE III method. The applicability and validity of this model were demonstrated using a case study. The case study compared the sustainability performance of a modular construction project, a semi-prefabrication one and a conventional cast-in-place one. Ranking results showed that semi-prefabrication project is the best option regarding sustainability level achieved, while modular project is ranked the second.